Beyond Swabian Spätzle-manufactures and trendy pubs – the political economy of gentrification (PROKLA. Journal of Critical Social Science, 2018)
Within public discourse, many journalists and other opinion makers often blame students, artists and hipsters as driving forces behind the displacement of working class households. Contrary to these popular explanation patterns, the essay argues that gentrification is a class struggle between those at risk of displacement and the agents of capital. To understand this struggle and the deeper causes of gentrification, critical urban studies offer a range of much more conclusive theoretical approaches and concepts – such as the rent gap theory, David Harvey’s urban political economy, and the neoliberalization of housing provision – to explain displacement processes, to reveal the fundamental social power relations, and to suggest strategies for resistance and political alternatives.